Determinants of legitimate governance of marine Natura 2000 sites in a post-transition European Union country: A case study of Puck Bay, Poland. (September 2016) - Piwowarczyk, Joanna; Wróbel, Borys
Abstract: This paper analyses the process of the creation of management plans for two marine protected areas in Puck Bay, Poland, belonging to the European Natura 2000 network. The review of documents, observations of public consultations and interviews with stakeholders allowed to identify the limitations of the process in terms of governance and legitimacy. Legitimacy—accountability of decision-makers; transparency and consistency of their decisions; and their consideration for the opinions of stakeholders—is a prerequisite for a wide support for conservation measures. Legitimate governance faces unique challenges in post-transition countries, such as Poland, where citizens tend to mistrust decision-makers and experts, and where the opinions of local citizens and municipalities were often ignored in the past. Because the creation of Natura 2000 sites—required under the EU Habitats and Birds Directives when Poland accessed to the EU—was not participatory, local communities consider these conservation measures as imposed and threatening their economic well-being. The analysis in this paper showed that transparency, consistency and accountability of the decision-making process could improve if the institutional responsibilities did not overlap, and if some key players, including the experts, did not play many, potentially conflicting, roles. The main conclusion is that the process is still based on bureaucratic and formal rules, even though a shift towards a more participative approach has started. Completing this shift will require replacing the participation rhetoric with participation practice, together with evidence-based decision making, and embracing openness and public debate on uncertainty. Highlights: Stakeholders in Natura 2000 sites do not know what is protected, where and why. Competences of many institutions in Poland overlap for marine sites in Puck Bay. A low level of transparency and accountability combines with the tradition of distrust. Experts and institutions fear public debate of uncertainty of scientific evidence. Openness and participation will lead to short-term tensions but more durable solutions.